2006
DOI: 10.1164/rccm.200506-934oc
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Pulmonary Inflammation in Cystic Fibrosis with Positron Emission Tomography

Abstract: Rationale: Although infection contributes to morbidity in patients with cystic fibrosis (CF), the host inflammatory response is also an important cause of progressive pulmonary function deterioration. Quantifying the inflammatory burden in these patients is challenging and often requires invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 38 publications
2
74
0
Order By: Relevance
“…Animal studies have shown that neutrophils are primary effectors of ''atelectrauma,'' (9, 32) and, in the setting of pulmonary inflammation, PET is a sensitive tool to detect the activation of these cells. Microautoradiography studies conducted both in animals (2,5,19,33) and in humans (20,21,34) suggest that uptake of 18 FDG occurs primarily by neutrophils. Furthermore, neutrophil depletion profoundly blunts the injury induced by mechanical ventilation (35) and the uptake of 18 FDG, albeit without abolishing it (3,36).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that neutrophils are primary effectors of ''atelectrauma,'' (9, 32) and, in the setting of pulmonary inflammation, PET is a sensitive tool to detect the activation of these cells. Microautoradiography studies conducted both in animals (2,5,19,33) and in humans (20,21,34) suggest that uptake of 18 FDG occurs primarily by neutrophils. Furthermore, neutrophil depletion profoundly blunts the injury induced by mechanical ventilation (35) and the uptake of 18 FDG, albeit without abolishing it (3,36).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PET has been shown to demonstrate pulmonary inflammation in infective pneumonia (38) and cystic fibrosis (39). Recently, there have been 2 small studies using 18 F-FDG PET (without CT) in IPF (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Even though pulmonary insufficiency remains the leading cause of morbidity and mortality in CF, the causes and manifestations of chronic airway inflammation appear to differ between CF patients (31)(32)(33)(34)(35). This interpatient variability could result from unique underlying CFTR defects, differences in microbial infection, the associated immune responses, environmental influences, and disease-modifying genes (36,37).…”
Section: Introductionmentioning
confidence: 99%